SOSIALISASI DAMPAK PENGGUNAAN AI UNTUK SISWA/I SMA YPK IMANUEL PASIR PUTIH - Joice Pangulimang; Yuliana Sangka; Yammes J. Batkunde; Jennis Tonapa; Irmawati Leppang; Engelberth Worabai; Mardewi; Levina Marthina Rumaropen; Nirmala (AMMA : Jurnal Pengabdian Masyarakat, 2026)
The use of Artificial Intelligence (AI) technology has both positive and negative impacts on students. AI can help students understand lessons, summarize material, and also encourage student independence in learning. However, this convenience has the potential to make students dependent on AI and decrease critical thinking skills. Therefore, it is important to conduct outreach about the use of AI in schools, especially YPK Imanuel Pasir Putih High School. The methods used in this community service are lectures and question and answer sessions. This activity aims to provide students with an understanding and wisdom in using AI. The result of this PKM activity is to increase high school students' awareness of utilizing AI technology as a learning tool.